Techno-ökonomischer Vergleich des Einsatzes von Strom, SNG und FT-Diesel aus Waldrestholz im Pkw-Bereich - Hurtig, Oliver (KIT Scientific Publishing, 2014)
Road traffic in Germany produces meaningful greenhouse gas (GHG) emissions and expends non-renewable resources. In an effort to locate alternative biofuel candidates, “second generation” biofuels produced from forest residues are investigated here. We developed a model to calculate and compare the technical, economic and environmental impacts, as well as technical and economic efficiency in reducing environmental impacts of these three fuels.